Stasis and Matters of Concern: The Conviction of the L'Aquila Seven. (April 2016) - DeVasto, Danielle; Graham, S. Scott; Zamparutti, Louise
On October 22, 2012, six scientists and one civil servant were convicted of manslaughter for failing to properly warn the people of L'Aquila, Italy, of an impending earthquake that resulted in over 300 deaths and 1, 500 injuries. This article investigates a key event leading up to this conviction: An emergency meeting of scientists, civil servants, and politicians to determine whether or not an advanced warning should be issued to the residents of L'Aquila. The following investigation of this emergency meeting uses functional stasis analysis to identify the primary breakdown in deliberation that ultimately led to a message of calm and reassurance immediately prior to the devastating earthquake. The results provide insights into not only the events in L'Aquila but also broader issues of risk, uncertainty, fact, and value in science-policy deliberation.